2006
DOI: 10.1080/01411920600635478
|View full text |Cite
|
Sign up to set email alerts
|

Can ICT reduce social exclusion? The case of an adults' English language learning programme

Abstract: Strong claims are made for ICT-based lifelong learning as an effective way of reducing the exclusion of various groups in society, yet, there is very little research to support these claims. Empirical research is needed, including qualitative studies of the experiences of socially excluded learners using ICT. This article reports the findings of such a study in relation to learners from one socially excluded group, adults from ethnic minority backgrounds, who are disproportionately deprived and often excluded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 27 publications
0
39
0
Order By: Relevance
“…Taken together, these studies support the notion that varieties of integrated TBLT and (Webb, 2006). Teachers planning to include technology in onsite instruction need to understand the extent to which students have access to computers; c) suplementary exercises for the language learning development, especially writing.…”
mentioning
confidence: 67%
“…Taken together, these studies support the notion that varieties of integrated TBLT and (Webb, 2006). Teachers planning to include technology in onsite instruction need to understand the extent to which students have access to computers; c) suplementary exercises for the language learning development, especially writing.…”
mentioning
confidence: 67%
“…In an examination of the role technology might play in reducing the exclusion of various groups within society, Webb (2006) concluded that 'For such learners, with supportive tutors, ICT-based learning was a medium that encouraged learners to imagine a future of greater inclusion in the host community' (p. 507). Such findings also reinforce the value of collaboration and the potential to form online communities of practice (Wenger, 1998).…”
Section: Collaborationmentioning
confidence: 98%
“…Studies have shown that ICT-based learning can reduce some aspects of social exclusion in terms of encouraging minority ethnic group learners to speak more within the host community (Webb, 2006). Noting the potential for migrant workers to use technology for learning (e.g., Kluzer, Ferrari, & Centeno, 2009), we investigate how migrant domestic workers use mobile technology to supplement formal learning at an open educational institution.…”
Section: Informal Digital Resources For Marginalized Populationsmentioning
confidence: 99%